Metabolite abundance in bovine preovulatory follicular fluid is influenced by follicle developmental progression post estrous onset in cattle - Hessock, Emma A.; Edwards, J. Lannett; Schrick, F. Neal; Payton, Rebecca R.; Campagna, Shawn R.; Pollock, Abigayle B.; Clark, Hannah M.; Stokes, Allyson E.; Klabnik, Jessica L.; Hill, Kennedy S.; Roberts, Samantha R.; Hinson, Meredith G.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Preovulatory follicle response to the luteinizing hormone (LH) surge leads to metabolic, molecular, and functional changes in the oocyte and somatic follicular cells from the onset of estrus to ovulation. Follicular fluid contains metabolites, miRNAs, proteins, and hormones that are byproducts of follicular metabolism and support cellular processes of oocyte, cumulus, and granulosa constituents. Numerous studies have highlighted the importance of follicular fluid composition to support fertility, but critical gaps exist toward understanding dynamic modifications in the follicular fluid metabolome from estrous onset to ovulation. The hypothesis was that abundance of follicular fluid metabolites is dependent on follicle progression post LH surge and variability in follicular fluid metabolome profiles indicate key processes required for preparation of the follicle and oocyte for optimal fertility. The objective was to generate preovulatory follicular fluid metabolome profiles and discern differences in the metabolome of preovulatory follicular fluid samples collected at onset of estrus, 11 h post estrous onset, and 18 h post estrous onset. Methods: Estrus was synchronized in non-lactating Jersey cows (n=40) and follicular fluid was collected immediately after the first observed standing mount (hr 0) or at approximately h 11 or 18 after the first standing mount. Ultra-High-Performance Liquid Chromatography-High Resolution Mass Spectrometry was performed on preovulatory follicular fluid samples (n = 9 collected at hr 0, 9 at h 11, and 10 at h 18) and a multiple linear model was performed to determine if time post estrous onset impacted metabolite abundance. Results: Metabolites influenced by time post estrous onset were tested for enrichment in KEGG pathways. Ninety metabolites were identified in follicular fluid samples. Twenty metabolites differed in abundance among timepoints post estrous onset (p ≤ 0.05). Pathways corresponding to amino acid and energy metabolism were enriched with metabolites impacted by time post estrous onset (FDR ≤ 0.10). Discussion: Results from the current study indicate early response to the LH surge to increase bioavailability of amino acids and metabolites used by the cumulus and granulosa cells for energy production and shuttled into the oocyte to support meiotic maturation. Such metabolites may later be used by the ovulatory follicle for protein production.